Optimal sizing and comparative analysis of rooftop PV and battery for grid-connected households with all-electric and gas-electricity utility. (15th July 2022) - Khezri, Rahmat; Mahmoudi, Amin; Whaley, David
Abstract: This study evaluates the optimal sizing and economic analysis of the rooftop solar photovoltaic (PV) and lithium-ion battery energy storage system (BESS) for grid-connected households. Two types of households are investigated, i.e., all-electric homes and those supplied with both gas and electricity. Each type of household is investigated under three system configurations: ( i ) without PV and BESS, ( ii ) with PV only, and ( iii ) with PV and BESS (PV-BESS) system. The objective is to minimize the net present value (NPV) of operating each type of house and examine the impact of the generation and storage technologies on these. For the all-electric household, gas demand is converted to electricity demand based on the gas and electric cooking and water heating appliance efficiencies used in this study. The houses NPVs are calculated using real monitored gas and electricity usage data, along with measured, solar irradiation and ambient air temperatures. It is found that the NPV varies for the all-electric and the gas and electric house, and is more prominent for the customers with gas and electric when no PV and BESS are installed. However, the key finding of this study highlights that the PV-BESS system is more economic for the all-electric houses. Highlights: Optimal sizing and comparison of PV-battery systems for two types of households. Practical optimal sizing by considering degradation, real data and supply of charge. Analyzing the impact of gas to electric conversion rate of efficiency. Considering the salvation value of components in the optimal sizing framework.